Data-driven regionalization for analyzing the spatiotemporal characteristics of air quality in China. (15th April 2019) - Wu, Chao; Hu, Wei; Zhou, Mengjie; Li, Sheng; Jia, Yan
Abstract: With the development of urbanization and industrialization, the degradation of air quality has become a serious issue that impacts human health and the environment; thus, it has attracted more attention from scholars. At present, the mass concentrations of sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), carbon monoxide (CO), ozone (O3 ) and particulate matter with an aerodynamic diameter less than 10 μm and 2.5 μm (PM10 and PM2.5 ) are used to evaluate air quality in China. A commonly used data-driven regionalization framework for studying air quality, identifying areas with similar air pollution behavior and locating emission sources involves an incorporation of the principal component analysis (PCA) with cluster analysis (CA) methods. However, the traditional PCA does not consider spatial heterogeneity, which is a notable issue in geographic studies. This article focuses on extracting the local principal components of air quality indicators based on a geographically weighted principal component analysis (GWPCA) method, which is superior to the PCA with considering spatial heterogeneity. Then, a spatial cluster analysis (SCA) is used to identify the areas with similar air pollution behavior based on the results of the GWPCA. The results are all visualized and show that the GWPCA has a higher explanatory ability than the traditional PCA. Our modified framework based on the GWPCA and SCA for assessing air quality can effectively guide environmentalists and geographers in evaluating and improving air quality from a spatial perspective. Furthermore, the visualization results can be used by city planners and the government for monitoring and managing air pollution. Finally, policy suggestions are recommended for mitigating air pollution via regional collaboration. Graphical abstract: Image 1 Highlights: The spatiotemporal patterns of air quality in 332 Chinese cities are analysed. GWPCA achieves more detailed results than PCA considering spatial heterogeneity. SKATER is used to identify the city clusters based on the results of GWPCA.